Development, nutrition, and rearing practices of relevant catfish species (Siluriformes) at early stages - Enric Gisbert; Ronald Kennedy Luz; Ignacio Fernández; Pravata K. Pradhan; Maria Salhi; Mansour T. Mozanzadeh; Aditya Kumar; Yannis Kotzamanis; Diana Castro‐Ruiz; Martin Bessonart; Maria J. Darias (Reviews in Aquaculture, 2022)
Catfish (Siluriformes) are important species for aquaculture worldwide, with an annual production in 2018 of ca . 6 million t. This review focuses on reassessing larval development, first feeding, and early rearing practices of the most important farmed catfish species, along with some candidate species for aquaculture diversification: Pangasianodon hypophthalmus (Pangasiidae), Clarias gariepinus (Clariidae), Ictalurus punctatus (Ictaluridae), Pseudoplatystoma spp. (Pimelodidae), Heteropneustes fossilis (Heteropneustidae), Rhamdia quelen (Heptapteridae), Ompok bimaculatus (Siluridae), and Lophiosilurus alexandri (Pseudopimelodidade). These species are initially reared indoors from one day to two weeks and are then transferred to fertilised outdoor ponds where they either feed on natural zooplankton or compound feeds. With the exception of C. gariepinus , I. punctatus , R. quelen and P. hypophthalmus , consistent and reliable fry production is a bottleneck that limits the expansion of farming of other species, such as Pseudoplatystoma spp., H. fossilis , O. bimaculatus , and L. alexandri . Rearing systems (extensive, semi‐extensive, intensive) and feeding protocols vary with species and geographical regions. Cannibalism and size heterogeneity are common, and these features create problems for larval and fry rearing of catfish species. Information about their nutritional requirements is required for the formulation of compound feeds that can guarantee high survival and good growth of catfish fries. However, such knowledge for most species is scarce, although some data are available for I. punctatus . Further genomic resources might allow fine‐tuning rearing success. This review describes some successes in this field, and also highlights gaps in knowledge to guide future research that can promote the development of catfish aquaculture.

The importance of pepsin‐like acid protease quantification in aquaculture studies: a revision of available procedures and presentation of a new protocol for its assessment - Héctor Nolasco‐Soria; Héctor‐Rodrigo Nolasco‐Alzaga; Enric Gisbert (Reviews in Aquaculture, 2020)
Assessing the activity of acid pepsin‐like protease is a common procedure in many biological, physiological and nutritional studies in gastric fish species. After reviewing the available literature on fish digestive acid proteases (stomach acid pepsin‐like proteases), especially those species of relevance for aquaculture purposes, published during a time span of ten years (2008–2018), authors detected some possible methodological and/or interpretative inconsistencies in this kind of studies when quantifying pepsin‐like enzymes. Thus, we concluded that special attention should be paid on the following issues when assessing digestive acid protease activity: (i) the proper preparation of stomach extracts, (ii) the use of the proper reaction conditions at the normal range of physiological pH and temperature values, and (iii) the proper quantification of the number of peptide bonds hydrolyzed for acid protease unit calculation. The implementation of these recommendations, and the proposal of more suitable (previously tested) methodological steps, will promote the standardization of acid pepsin‐like protease analytical procedures, as well as improve the reliability of comparative studies dealing with this proteolytic enzyme between different fish species of aquacultural importance.

New developments and biological insights into the farming of Solea senegalensis reinforcing its aquaculture potential - Sofia Morais; Cláudia Aragão; Elsa Cabrita; Luís E.C. Conceição; Maria Constenla; Benjamín Costas; Jorge Dias; Neil Duncan; Sofia Engrola; Alicia Estevez; Enric Gisbert; Evaristo Mañanós; et al. (Reviews in Aquaculture, 2016)
Senegalese sole was one of the earliest identified candidate species with high potential for aquaculture diversification in the south of Europe. Its culture has been possible, and commercially attempted, for several decades, but intensive production has been slow to take off. This has been explained mostly by serious disease problems, high mortality at weaning, variable growth and poor juvenile quality. However, a strong and sustained research investment that started in the eighties has led to a better understanding of the requirements and particularities of this species. More recently, better management and technical improvements have been introduced, which have led to important progress in productivity and given a new impetus to the cultivation of Senegalese sole. As a result, the last 5 years have marked a probable turning point in the culture of sole towards the development of a knowledge‐driven, competitive and sustainable industry. This review will focus on the main technical improvements and advances in the state of knowledge that have been made in the last decade in areas as diverse as reproductive biology, behaviour, physiology, nutritional requirements, modulation of the immune system in response to environmental parameters and stress, and characterization and mitigation of the main disease threats. It is now clear that Senegalese sole has important particularities that differentiate it from other current and candidate marine aquaculture species, which bring about important challenges, some still unsolved, but also notable opportunities (e.g. a nutritional physiology that is better adapted to dietary vegetable ingredients), as will be discussed here.

Pilot acoustic tracking study on adult spiny lobsters (Palinurus mauritanicus) and spider crabs (Maja squinado) within an artificial reef - Guiomar Rotllant; Jacopo Aguzzi; David Sarria; Enric Gisbert; Valerio Sbragaglia; Joaquín Del Río; Carles G. Simeó; Antoni Mànuel; Erik Molino; Corrado Costa; Francisco Sardà (Hydrobiologia, 2015)

Skeletal anomalies in reared E uropean fish larvae and juveniles. Part 1: normal and anomalous skeletogenic processes - Clara Boglione; Paulo Gavaia; Giorgos Koumoundouros; Enric Gisbert; Mari Moren; Stéphanie Fontagné; Paul Eckhard Witten (Reviews in Aquaculture, 2013)
This critical review summarizes the knowledge about fish skeletal tissues and inherent normal and anomalous development. Particular emphasis is given to existing literature on reared European fishes. The aim was to identify the main gaps of knowledge that require to be filled, in order to precociously identify anomalous developmental patterns that lead to skeletal anomalies in reared finfish larvae and juveniles. The review also aims to extend our knowledge about the factors that are possibly involved in the onset of skeletal anomalies. The final goal is the optimization of the morphological quality of farmed juvenile fish.

Skeletal anomalies in reared E uropean fish larvae and juveniles. Part 2: main typologies, occurrences and causative factors - Clara Boglione; Enric Gisbert; Paulo Gavaia; Paul E. Witten; Mori Moren; Stéphanie Fontagné; Giorgos Koumoundouros (Reviews in Aquaculture, 2013)
The presence of skeletal anomalies in farmed teleost fish is currently a major problem in aquaculture, entailing economical, biological and ethical issues. The common occurrence of skeletal abnormalities in farmed fish and the absence of effective solutions for avoiding their onset or definitely culling out the affected individuals as early as possible from the productive cycle, highlight the need to improve our knowledge on the basic processes regulating fish skeletogenesis and skeletal tissues differentiation, modelling and remodelling. Severe skeletal anomalies may actually occur throughout the entire life cycle of fish, but their development often begins with slight aberrations of the internal elements. Comprehensive investigation efforts conducted on reared larvae and juveniles could provide a great contribution in filling the gap in knowledge, as skeletogenesis and skeletal tissue differentiation occur during these early life stages. The aim of this review is to provide a synthetic but comprehensive picture of the actual knowledge on the ontogeny, typologies and occurrence of skeletal anomalies, and on the proposed causative factors for their onset in larvae and juveniles of E uropean farmed fish. The state‐of‐art of knowledge of these issues is analysed critically intending to individualize the main gaps of knowledge that require to be filled, in order to optimize the morphological quality of farmed juveniles.